Formation of 3-dimensional gold, copper and palladium microelectrode arrays for enhanced electrochemical sensing applications - Hay, Catherine; Lee, Juni; Silvester-Dean, Debbie (MDPI, 2019)
Microelectrodes offer higher current density and lower ohmic drop due to increased radial diffusion. They are beneficial for electroanalytical applications, particularly for the detection of analytes at trace concentrations. Microelectrodes can be fabricated as arrays to improve the current response, but are presently only commercially available with gold or platinum electrode surfaces, thus limiting the sensing of analytes that are more electroactive on other surfaces. In this work, gold (Au), copper (Cu), and palladium (Pd) are electrodeposited at two different potentials into the recessed holes of commercial microelectrode arrays to produce 3-dimensional (3D) spiky, dendritic or coral-like structures. The rough fractal structures that are produced afford enhanced electroactive surface area and increased radial diffusion due to the 3D nature, which drastically improves the sensitivity. 2,4,6-trinitrotoluene (TNT), carbon dioxide gas (CO2), and hydrogen gas (H2) were chosen as model analytes in room temperature ionic liquid solvents, to demonstrate improvements in the sensitivity of the modified microelectrode arrays, and, in some cases (e.g., for CO2 and H2), enhancements in the electrocatalytic ability. With the deposition of different materials, we have demonstrated enhanced sensitivity and electrocatalytic behaviour towards the chosen analytes.